Pemanfaatan Sistem Cloud Accounting untuk Training Online WBAS Jurusan Akuntansi Pada Universitas Raharja - Qurotul Aini; Alwiyah Alwiyah; Cheetah Savana Putri (Universitas Raharja, 2019)
The progress of globalization that is applying technology and information is very rapid, encouraging various educational institutions and agencies to be able to utilize online training systems to increase flexibility and effectiveness in conducting training / training / learning processes, especially in distance education. In terms of this training, it is felt that now it has to follow the times. In terms of making it easier for students to take part in training and facilitate trainers to manage the results of the training that has been carried out by the training participants. However, in some educational institutions and agencies there is still no online training system. This will cause 3 (three) problems, namely: Training still uses conventional methods, educational institutions do not provide open source software, long queues. In preventing the above problems, it is necessary to use online training using Jurnal.id software which will make it easier for students to carry out the training. These problems are the background for the establishment of a system of utilization of cloud accounting for online Web-Based Accounting System (WBAS) training with the aim of facilitating training participants and students in conducting online training expected to improve the quality of education for accounting students and trainees to be able to be more effective and flexible in training. In the utilization of Cloud Accounting, it is expected to be able to become a system as a storage of accounting with online or online media making it easier for students and trainees to carry out accounting training online